2020
DOI: 10.1186/s12944-019-1180-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia triggered acute pancreatitis in pregnancy – diagnostic approach, management and follow-up care

Abstract: Acute pancreatitis is a pregnancy complication potentially lethal for both the mother and fetus, occurring most frequently in the third trimester or early postpartum. Hypertriglyceridemia may be the cause of important disease in pregnant patients. Patients with triglyceride levels exceeding 1000 mg/dL are at increased risk of developing severe pancreatitis. Diagnostic criteria and management protocols are not specific for pancreatitis complicating pregnancy. Other causes of acute abdominal pain must be conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 57 publications
(58 reference statements)
1
35
0
4
Order By: Relevance
“…3 Biliary pancreatitis is the primary etiology cause of AP in general population, accounting for 40-70%, while HTG-AP is only 2-4%. 28 Different from the general population, the incidence of HTG-AP in pregnancy was much higher, 11,29 which reached 29.6-32.2% in several recent studies from East Asia. 13,16,30 In the present study, HTG-AP was the primary cause, accounting for 47%.…”
Section: Discussionmentioning
confidence: 91%
“…3 Biliary pancreatitis is the primary etiology cause of AP in general population, accounting for 40-70%, while HTG-AP is only 2-4%. 28 Different from the general population, the incidence of HTG-AP in pregnancy was much higher, 11,29 which reached 29.6-32.2% in several recent studies from East Asia. 13,16,30 In the present study, HTG-AP was the primary cause, accounting for 47%.…”
Section: Discussionmentioning
confidence: 91%
“…Hypertriglyceridemia may be the cause of important disease in pregnant patients. Patients with triglyceride levels exceeding 1,000 mg/dl are at increased risk of developing severe pancreatitis (Cruciat et al, 2020). Some studies reported that 54.1% (33/61) of the SAP patients had a high CrCl (more than 130 ml/min/1.73 m 2 ), and the serum trough concentration of vancomycin was significantly reduced in SAP patients with ARC (He et al, 2016;He et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Polygenic inheritance of multiple genes results in more common but milder levels of hypertriglyceridemia. Secondary factors such as insulin resistance, hypothyroidism, and glucocorticoids also play an important role ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Complication rates (peripancreatic collections, necrotizing pancreatitis) are twice as high in hypertriglyceridemia-induced pancreatitis ( 4 ). In pregnancy, hypertriglyceridemia-induced pancreatitis is associated with a higher risk of organ failure and intensive care support, and fetal loss, preterm labor, pre-eclampsia, and abruptio placentae ( 3 , 4 ). The accumulation of lipids also increases the risk of fetal macrosomia resulting in pre-term delivery ( 5 ).…”
Section: Discussionmentioning
confidence: 99%